2016
DOI: 10.3892/ijo.2016.3688
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of RPL9 expression inhibits colorectal carcinoma growth via the inactivation of Id-1/NF-κB signaling axis

Abstract: Ribosomal protein L9 (RPL9), a component of the 60S subunit for protein synthesis, is upregulated in human colorectal cancer. In the present study, we investigated whether RPL9 gained extraribosomal function during tumorigenesis and whether targeting of RPL9 with small interfering (si) RNA could alter the course of colorectal cancer progression. Our results showed that siRNA knockdown of RPL9 suppresses colorectal cancer (CRC) cell growth and long-term colony formation through an increase in sub-G1 cell popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…12 Furthermore, it has been found in gastric cancer and pancreatic cancer cells that the Id-reverse target-nuclear factor κB (NF-κB) pathway is activated to promote the expression of Bcl-2, inhibit the TNF-ɑ pathway, decrease the expression level of caspase-3, and inhibit tumor cell death. [13][14][15] In this present study, an interference sequence of Id-1 was introduced into SW480 and HT-29 colon cancer cells, and it was found through MTT detection that proliferation began to decrease in the inhibition groups from the third day, and the growth inhibition in the inhibition groups was obvious from the fourth day. This reveals that the proliferation ability of cells significantly decreased in the inhibition groups, proving that Id-1 can promote colon cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…12 Furthermore, it has been found in gastric cancer and pancreatic cancer cells that the Id-reverse target-nuclear factor κB (NF-κB) pathway is activated to promote the expression of Bcl-2, inhibit the TNF-ɑ pathway, decrease the expression level of caspase-3, and inhibit tumor cell death. [13][14][15] In this present study, an interference sequence of Id-1 was introduced into SW480 and HT-29 colon cancer cells, and it was found through MTT detection that proliferation began to decrease in the inhibition groups from the third day, and the growth inhibition in the inhibition groups was obvious from the fourth day. This reveals that the proliferation ability of cells significantly decreased in the inhibition groups, proving that Id-1 can promote colon cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, it has been found in bone cell cancer that Id‐1 activates cell growth and promotes cell proliferation by activating the MAPK of Raf‐1 . Furthermore, it has been found in gastric cancer and pancreatic cancer cells that the Id‐reverse target‐nuclear factor κB (NF‐κB) pathway is activated to promote the expression of Bcl‐2, inhibit the TNF‐ɑ pathway, decrease the expression level of caspase‐3, and inhibit tumor cell death . In this present study, an interference sequence of Id‐1 was introduced into SW480 and HT‐29 colon cancer cells, and it was found through MTT detection that proliferation began to decrease in the inhibition groups from the third day, and the growth inhibition in the inhibition groups was obvious from the fourth day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these GO terms, ribosomal, RNA, and ubiquitin related are among the pathways holding the highest statistical significance. Ribosomal proteins are most commonly known to be involved in protein synthesis but have also been shown to exert extraribosomal functions including immune signaling and development of various cell types as well as being implicated in various cancers including glioblastoma, gastrointestinal, prostate, and lung . In this study, expression levels of many genes, encoding ribosomal proteins (Rp), were found to be differentially regulated in both Tpm1.12‐ and Tpm2.1‐overexpressing cells including Rpl9, Rpl13, Rpl19, and Rpl22 .…”
Section: Resultsmentioning
confidence: 77%